Dorothy Richardson’s Poetic Works - Alijonova Okila (Periodica Journal, 2022)
This article is dedicated to the poetic works of Dorothy Richardson. The concept of woman, displayed in the poetess's work, is part of the picture of her imaginary world. It should be noted that it is broader than the primary concept, because it includes D. Richardson's personal experience. At the same time, it provides what was mentioned earlier: the concept of the poetess reflects the position of the author, but the national concept has not completely disappeared, both concepts overlap with each other.
Keywords: Concept Of Woman; Poetic; Imaginary World; Character